Memotret Pola Keberagamaan Masyarakat Samin di Desa Klopoduwur Kecamatan Banjarejo Kab. Blora - Anwar, Sholihul (JURNAL PEDAGOGY, 2018)
Pattern is a form whereas religiosity is an activity related to religion and also a comprehensive unit of unity, which makes a person called a religious person and not merely claiming to have a religion. Society of samin who is generally known to have unique character and teachings and become one of the academic spotlight in social, cultural and phenomena as a traditional community that needs to be understood together. The author is interested in studying in this article in the form of literature taken based on qualitative descriptive analytic approach. The focus of this article is how the portrait of religious patterns of the samin community in Klopoduwur Village, Banjarejo District Blora in understanding the teachings of religion in life according to the provisions of Islam as a religion that is adhered to the public samin in general now diera Based on the analysis of descriptive writer can be seen that the portrait of religious patterns of the claminic community Klopoduwur Village Banjarejo District Blora Regency, including: First, the Islamic historical perspective that is applied in the religious practice of the samin community is Islamic tradition / Islamic culture. Samin community as a traditional group are those who tend to understand the shari'ah as has been practiced by the previous scholars still hold the religious norms according to local thinking and culture and social conditions that exist. Secondly, the religion of the samin community with the term Islam is different from the syncretic practices that are common among Javanese society. inspired from his understanding that the first person inhabiting this universe was Adam, followed by Howo's mother. The birth of Adam and Howo's mother because of Yai's sole sabu as sole ruler. The existence of Yai because of Adam. Yai according to understanding the teachings of samin is God Almighty or Allah Almighty. for Muslims. Thirdly, the Samin community has different understanding and practice of worship, such as (1) the mortification of the corpses, the corpses are not always bathed and unmixed, although they are worshiped as the majority religion in their environment (Islam), (2) slaughter of self-patterned animals, especially in the case of slaughtering prayers , (3) traditionalize the suro fasting and fasting of the birth day. The semedi beliefs are believed in the community's acculturation samination from the Hindu teaching or the syncretism as a form of prayer and cultivating inner energy and honor to God Almighty. So the religious practice that became the religious pattern of the Samin community experienced the reduction and adaptation of the existing culture in the surrounding Javanese society